Foot-and-mouth disease virus replicates independently of phosphatidylinositol 4-phosphate and type III phosphatidylinositol 4-kinases - Berryman, Stephen; Moffat, Katy; Harak, Christian; Lohmann, Volker; Jackson, Terry (Journal of general virology, 2016)
Picornaviruses form replication complexes in association with membranes in structures called replication organelles. Common themes to emerge from studies of picornavirus replication are the need for cholesterol and phosphatidylinositol 4-phosphate (PI4P). In infected cells, type III phosphatidylinositol 4-kinases (PI4KIIIs) generate elevated levels of PI4P, which is then exchanged for cholesterol at replication organelles. For the enteroviruses, replication organelles form at Golgi membranes in a process that utilizes PI4KIIIβ. Other picornaviruses, for example the cardioviruses, are believed to initiate replication at the endoplasmic reticulum and subvert PI4KIIIα to generate PI4P. Here we investigated the role of PI4KIII in foot-and-mouth disease virus (FMDV) replication. Our results showed that, in contrast to the enteroviruses and the cardioviruses, FMDV replication does not require PI4KIII (PI4KIIIα and PI4KIIIβ), and PI4P levels do not increase in FMDV-infected cells and PI4P is not seen at replication organelles. These results point to a unique requirement towards lipids at the FMDV replication membranes.,
Gesehen am 07.05.2020